2015
DOI: 10.1007/s00277-015-2381-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of nilotinib therapy after imatinib failure in eosinophilic myeloproliferative neoplasm and ETV6-ABL rearrangement

Abstract: Dear Editor, The ETV6 gene, previously known as TEL, is a member of the ETS family of transcription factors located at 12p13. Its role in leukemogenesis was initially estabilished as a fusion partner to the PDGFR-beta gene in a case of chronic myelomonocytic leukemia with t (5;12)(q33;p13) [1]. The ETV6-ABL gene product has been demonstrated to have tyrosine kinase activity remarkably similar to that of BCR-ABL, despite the fusion partners for ABL being completely different [2]. Several studies proved the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Definitive evidence of the prognostic influence of the ETV6-ABL1 fusion in haematological neoplasms is lacking; however, overall data suggests that it is a poor prognostic factor, particularly in patients with ALL and AML [1,12]. There also are no definitive data to standardize the treatment for ETV6-ABL1 MPNs, although multiple reports advocate for the early introduction of first and/or second generation TKIs [13][14][15]. Recently, Zhang et al published a retrospective series of 42 adult patients with a confirmed myeloproliferative neoplasm associated with eosinophilia and a tyrosine kinase gene fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Definitive evidence of the prognostic influence of the ETV6-ABL1 fusion in haematological neoplasms is lacking; however, overall data suggests that it is a poor prognostic factor, particularly in patients with ALL and AML [1,12]. There also are no definitive data to standardize the treatment for ETV6-ABL1 MPNs, although multiple reports advocate for the early introduction of first and/or second generation TKIs [13][14][15]. Recently, Zhang et al published a retrospective series of 42 adult patients with a confirmed myeloproliferative neoplasm associated with eosinophilia and a tyrosine kinase gene fusion.…”
Section: Discussionmentioning
confidence: 99%
“…We identified an additional 14 cases in the literature [16–27,53,54] with adequate data on response on TKI and follow‐up. In concordance with our findings, imatinib can induce but not maintain long‐term remissions 25 . Unfortunately, only limited data on TK‐domain mutations are available which might explain the lack of response to and early progression on imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…Beside ALL, the phenotype may resemble in adults a myeloid neoplasm such as atypical chronic myeloid leukemia (aCML), chronic eosinophilic leukemia (CEL), myelodysplastic/myeloproliferative neoplasm unclassified (MDS/MPN‐U) or MPN‐U which are diagnosed in CP or BP. However, data on treatment and response to ABL1 inhibitors such as imatinib, nilotinib or dasatinib are limited to case reports or small cases series 16‐27 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation